Combination of Silica (SiO2) Addition from Rice Husk As a Heat-Resistant Coating Material at Wall Paint - Dafit Ericson Sihotang; Putri Yanita Sidabutar; Lisnawaty Simatupang (Universitas Negeri Medan, 2025)
The synthesis of silica gel from rice husk ash has been carried out using the sol-gel method, which is mixed into paint as an additive for heat resistance. This research aims to determine the combination of adding SiO2 additive to wall paint as a heat-resistant coating material. The characterization methods used are FTIR, XRD, and SEM. The initial stage of this research involves the synthesis of silica gel from rice husk ash, which is then mixed into 10 mL of paint with varying silica additions of 0.1; 0.2; 0.3; 0.4; and 0.5 grams. After that, it is tested for heat absorption. Based on the FTIR results on silica, silanol (Si-OH) and siloxane (Si-O-Si) groups were observed, and the XRD results indicated that the silica structure produced was amorphous.